Design of Driver’s Display Unit Based on Dual Network Redundancy in CR200J Centralized Power EMUs - Lu LU; feng JIA; Qingqiang ZHOU; Yang SONG; Xin ZHAO; Lei GAO (机车电传动)
According to the communication requirements of CR200J EMUs microcomputer network control system, the design of man-machine interface based on MVB and ethernet dual network redundancy was proposed, and the specific solution was described in detail. Starting from the technical indicators of software, hardware and dual network communication, the functional structure diagram of man-machine interface was introduced, focusing on the key interface design based on dual network redundancy, and leading to the innovation of data display and processing mechanism of all network sub equipment in the case of dual network. The test results showed that the display screen of this design scheme has stable operation, friendly interface, perfect function, which meet the design requirements, and improved the reliability and safety of locomotive operation.